COVID-19: gender characteristics of the course, perinatal risks and possible ways to prevent complications - I.A. Zhabchenko; I.S. Lishchenko; N.V. Gerevich (Publishing House TRILIST, 2021)
The article contains modern data of the characteristics, course and impact on pregnant women, postpartum women, fetus and newborn of the SARS-CoV-2. The opinions of experts from different countries of the world on the consequences of coronavirus disease depending on racial, ethnic, age differences and delivery time. Immunological and hormonal protection during pregnancy against viral influences is noted. In the context of a pandemic, the number of premature births (for various reasons) and the birth of children with low birth weight significantly increased, but their relationship with COVID-19 infection has not been proven. Risk factors for the hospitalization of pregnant woman infected with COVID-19 are high body mass index, obesity and concomitant diseases (diabetes mellitus, hypertension. Women in older reproductive age also need hospitalization more often. During pregnancy, innate and adaptive immune responses shift from an inflammatory to an anti-inflammatory phenotype to prevent affection of the fetus and promote passive transmission of maternal antibodies to the fetus. These COVID-19 protection effects are largely mediated by estradiol and progesterone. New data on the impact of COVID-19 on erythropoiesis, hemoglobin and ferritin levels are presented, and risk groups of a more severe course of the disease are identified: elderly adults, patients, patients with arterial hypertension, obesity and diabetes mellitus, pregnant women, patients with primary and acquired immunodeficiency, with oppression of the hematopoiesis, HIV-infected and with cancer. The algorithm of outpatient monitoring of pregnant women during a pandemic (self-assessment of the state, online control, etc.) is given. Some current world protocols for the COVID-19 prevention and treatment have been analyzed and a modification adapted for Ukrainian pregnant women has been proposed. A method is proposed for the prevention miscarriage and nutritional deficits - one of the frequent and dangerous COVID-19 complications in pregnant women.